TiO𝟐-Based Organic Hybrid Solar Cells with Mn+𝟐 Doping - Zühal Alparslan; Arif Kösemen; Osman Örnek; Yusuf Yerli; S. Eren San (International Journal of Photoenergy)
A hybrid solar cell is designed and proposed as a feasible and reasonable alternative, according to acquired efficiency with the employment of TiO2 (titanium dioxide) and Mn-doped TiO2 thin films. In the scope of this work, TiO2 (titanium dioxide) and Mn:TiO2 hybrid organic thin films are proposed as charge transporter layer in polymer solar cells. Poly(3-hexylthiophene):phenyl-C61-butyric acid methyl ester (P3HT: PCBM) is used as active layer. When the Mn-doped TiO2 solar cells were compared with pure TiO2 cells, Mn-doped samples revealed a noteworthy efficiency enhancement with respect to undoped-TiO2-based cells. The highest conversion efficiency was obtained to be 2.44% at the ratio of 3.5% (wt/wt) Mn doping.